Control of a recuperative vapor- recompression air separation process. (September 2016) - Luyben, William L.
Highlights: Dynamic model developed for air separation unit using vapor recompression. Conventional and on-demand control structures explored. Control of a coupled process with the ASU feeding a furnace investigated. Abstract: The use of oxy-combustion for producing furnace stack gases with low nitrogen and high carbon dioxide concentrations is a potential method for economical sequestration of green house gases. A conventional air separation unit to provide oxygen compresses all the air feed and operates with one of the two cryogenic distillation columns at elevated pressure so heat integration can be employed. The use of recuperative vapor recompression has been recently proposed in which only a portion of a nitrogen stream is compressed to provide liquid reflux to two columns, which both operate at low pressure where the separation is easier. Steady-state designs have been developed and economically optimized. The purpose of this paper is to explore the dynamic controllability of this type of vapor recompression system for air separation.